Analysis of cylindrical pressure vessels with dissimilar ends and material comparison. (2022) - Kushwah, Sagarsingh; Parekh, Shreyashkumar; Mistry, Harsh; Darji, Jainil; Gandhi, Rutvik
Abstract: The current work deals with the methodological study of pressure vessel (Cylindrical or spherical) with different ends or heads. The pressure vessel is designed for 24 L volume and 8 bar pressure vessels are done following ASME standard section VIII, Division I. The thickness of all cylindrical heads is calculated by different formulae and the thickness vary accordingly. However, in this project, the thickness is kept constant irrespective of cylindrical heads or ends to study its effect. FEA is performed to evaluate or study the stress parameters. The software took for Finite Element Analysis (FEA) in Ansys 19.2. Before that, the 3D modelling was done using SolidWorks software. After concluding the better cylindrical end or head for constant thickness, the comparison of the material is made to compare with the current state of the art and find out the better material by analyzing the circumferential stress and longitudinal stress.